Secondary battery

By mixing olivine structural materials with layered structure materials in the positive electrode sheet of secondary batteries, the battery's safety and thermal stability are enhanced, addressing the low safety performance of ternary secondary batteries.

JP2025070918AActive Publication Date: 2025-05-02AESC JAPAN LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023208525
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2023-12-11
Publication Date
2025-05-02
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

Ternary secondary batteries exhibit low safety performance due to poor high temperature performance, cycling performance, and structural stability compared to lithium-ion iron phosphate batteries.

Method used

A secondary battery design incorporating a positive electrode sheet with a mixture of layered structure and olivine structural materials, where the mass ratio of the second active material (olivine) to the total mass of both active materials ranges from 5% to 30%, introducing a two-stage discharge voltage platform.

Benefits of technology

The battery achieves improved voltage and capacity, reduced discharge depth of the layered structure material, enhanced thermal stability, and increased safety performance by transitioning from a higher to a lower voltage platform during discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070918000001_ABST
    Figure 2025070918000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery which uses a three-dimensional material as a positive electrode material and can improve the safety performance.SOLUTION: The secondary battery includes a positive electrode sheet, a separator, and a negative electrode sheet. The positive electrode sheet has a positive electrode material including a first active material and a second active material. The first active material is a layered structural material, and the second active material is an olivine structural material. The mass ratio of the second active material to the sum of masses of the first active material and the second active material is in the range of 5 wt.%-30 wt.%. The discharge curve of the secondary battery has a first voltage platform and a second voltage platform.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of secondary batteries, and more particularly to secondary batteries. [Background technology]

[0002] With the progress of science and technology and the increasing need for environmental protection improvement, electrochemical devices (such as lithium-ion batteries) are becoming more prevalent in people's daily lives. As lithium-ion batteries become more popular, their safety performance has been attracting more attention, especially due to fire and explosion accidents in electric vehicles. As a result, users, after-sales personnel, and lithium-ion battery manufacturers are all raising new requirements for the safety performance of lithium-ion batteries. In this regard, various countries will also introduce stricter laws and regulations. Based on the current safety situation of lithium batteries, some improved designs need to be made to enhance the safety of lithium batteries.

[0003] At present, ternary materials are used as the positive electrode material of lithium ion batteries, and ternary materials have excellent advantages such as high energy density, high voltage platform, ideal crystal structure, small self-discharge, no memory effect, etc. Ternary materials are currently commonly used in lithium ion batteries. However, the high temperature performance of ternary materials is defective, and the rate performance and structural stability of ternary materials are not as favorable as lithium iron phosphate. Therefore, the produced ternary material lithium ion batteries have inferior high temperature performance, cycle performance and structural stability compared with lithium iron phosphate ion batteries.

[0004] Therefore, in order to solve the above problems, there is a need to design a secondary battery that can improve the safety performance of batteries that use ternary materials as the main positive electrode materials. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above-mentioned shortcomings of the related art, the present invention provides a secondary battery that solves the technical problem of the poor safety performance of currently available ternary secondary batteries. [Means for solving the problem]

[0006] In order to achieve the above and other related objectives, the present invention provides a secondary battery including a positive electrode sheet, a separator, and a negative electrode sheet. The positive electrode sheet includes a positive electrode material including a first active material and a second active material.

[0007] Here, the first active material is a layered structure material. The second active material is an olivine structure material. The mass ratio of the second active material to the total mass of the first active material and the second active material is 5% by weight to 30% by weight. The discharge curve of the secondary battery has a first voltage platform and a second voltage platform. The measured voltage y of the secondary battery is y1 min <y<y1 max Or y2 min <y<y2 max and y1 and y2 satisfy the formulas (1) and (2). y1=0.5265a+d (1) y2=-0.5265b+c (2) In the formula, a is the mass ratio of the first active material to the sum of the masses of the first active material and the second active material, b is the mass ratio of the second active material to the sum of the masses of the first active material and the second active material, c is a first voltage platform at which the first active material participates in the discharge, the first voltage platform being 3.7143V to 3.7743V, and d is a second voltage platform at which the second active material participates in the discharge, the second voltage platform being 3.1878V to 3.2478V.

[0008] In one embodiment of the present invention, the curve ratio value of the second active material involved in the discharge in the discharge curve is 80% to 87% of the mass proportion b.

[0009] In one embodiment of the present invention, the curve ratio of the second active material involved in the discharge curve is 4% to 25%.

[0010] In one embodiment of the present invention, the layered structure material is LiNi x Co y M 1-x-y O2, where 0 < x < 1, 0 < y < 1, and the element M includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, Ta.

[0011] In one embodiment of the present invention, the olivine structure material is LiFe z G 1-z PO4, where 0 < z < 1, and the element G includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, Ta.

[0012] In one embodiment of the present invention, the average particle diameter D50 of the first active material is 0.5 μm to 5 μm, and the average particle diameter D50 of the second active material is 0.3 μm to 3 μm.

[0013] In one embodiment of the present invention, the first active material is single crystal and / or polycrystal.

[0014] In one embodiment of the present invention, the degree of orientation of the positive electrode sheet is 70 to 99, and the degree of orientation of the negative electrode sheet is 10 to 60.

[0015] In one embodiment of the present invention, the compression density of the positive electrode sheet is 3.0 g / cm 3 ~3.6 g / cm 3 and the surface density coated on one side of the positive electrode sheet is 0.014 g / cm 2 ~0.02 g / cm 2 is.

[0016] In one embodiment of the present invention, the compression density of the negative electrode sheet is 1.1 g / cm 3 ~1.7 g / cm 3 and the surface density coated on one side of the negative electrode sheet is 0.008 g / cm 2 ~0.013 g / cm 2 is.

Advantages of the Invention

[0017] In the secondary battery provided by the present invention, a two-stage discharge voltage platform is introduced during the discharge process of the secondary battery by mixing an olivine structure material with a positive electrode material mainly composed of a layered structure material. In this way, the secondary battery can transition from discharging at a higher first voltage platform to discharging at a lower second voltage platform during discharge. As a result, the voltage and capacity of the secondary battery are improved, while the discharge depth of the layered structure material is reduced, thereby improving the thermal stability of the secondary battery. Thermal runaway of the battery during overcharging and discharging is prevented, and the safety performance of the secondary battery is improved. Therefore, the present invention can effectively solve some practical problems in the prior art, and can exert high utility value and utility significance. [Brief description of the drawings]

[0018] In order to more clearly show the technical solutions provided in the embodiments of the present invention or related technologies, some accompanying drawings necessary for the description in the embodiments or related technologies are briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Figure 1] 1 is a graph of discharge curve testing of secondary batteries according to some embodiments of the present invention. [Diagram 2] 4 is a graph showing the relationship between the measured voltage and the mass fraction of the first active material of secondary batteries according to some embodiments of the present invention. [Diagram 3] 4 is a graph showing the relationship between the measured voltage and the mass fraction of a second active material of a secondary battery according to an embodiment of the present invention. [Figure 4] 2 is an XRD test graph of a positive electrode sheet of a secondary battery according to an embodiment of the present invention. [Diagram 5] 2 is an XRD test graph of a negative electrode sheet of a secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The implementation of the present invention will be described below through a specific embodiment. Those skilled in the art can easily understand other advantages and effects of the present invention from the disclosure of this specification. The present invention can also be implemented or applied through other different specific implementation methods. The details of this specification can also be modified or changed based on different perspectives and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features of each embodiment can be combined if they are not inconsistent. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific implementations and are not intended to limit the scope of protection of the present invention. It should be noted that the test methods not specifically indicated in the following embodiments usually follow conventional conditions or conditions provided by each manufacturer.

[0020] In addition, terms such as "upper", "lower", "left", "right", "middle", and "one side" used in this specification are described solely for the convenience of explanation and are not used to limit the scope of application of the present invention. Cases in which the relative relationship is changed or adjusted without substantially changing the technical content are also included in the scope of application of the present invention.

[0021] Through research, the inventors have found that although the secondary battery using the ternary laminated material as the positive electrode material has the advantages of high energy density and high discharge voltage platform, there is a hidden danger of the safety performance of the secondary battery due to the poor thermal stability of the ternary material. Specifically, during the over-discharge process at high voltage, the Ni in the ternary material 4+ Ion is Ni 2+ At the same time, to maintain charge neutrality, O 2- is oxidized and escapes from the crystal lattice. The escape of a large amount of oxygen creates a large amount of oxygen vacancies, which reduces the activation energy barrier for the migration of transition metal cations and accelerates the phase transition process of the material from layered structure to spinel structure and rock salt structure. The release of oxygen and the structural deterioration of the positive electrode material form a vicious cycle, which affects the thermal runaway temperature of the battery. As a result, the thermal stability of the battery is reduced, leading to safety risks.

[0022] Therefore, it can be seen that when the positive electrode material is in a higher discharge voltage platform for a long period of time during the discharge process, the irreversible structure collapse of the layered structure material is aggravated. The layered structure material generates a large amount of gas when the structure collapses, lowering the activation energy barrier. This causes the layered structure of the positive electrode material to continue to collapse during the discharge process, resulting in a rapid decrease in the thermal runaway temperature of the battery.

[0023] Therefore, the present invention provides a secondary battery to solve the above problems. In the secondary battery, an olivine structure material is mixed into a positive electrode material mainly made of a layered structure material. By mixing the olivine structure material into the layered structure material, the storage voltage capacity of the secondary battery is improved, and at the same time, a two-stage discharge voltage platform is introduced during the discharge process. During discharge, the secondary battery can transition from discharging at a higher first voltage platform to discharging at a lower second voltage platform. In this way, the discharge depth of the layered structure material is effectively reduced under the high voltage platform, the structural thermal stability of the positive electrode material is improved, and the rapid drop in the thermal runaway temperature of the battery due to overdischarge is avoided.

[0024] The present invention provides a secondary battery including a positive electrode sheet, a negative electrode sheet, an electrolyte, a separator, corresponding communication accessories, and a circuit. Here, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer includes a positive electrode material. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer includes a negative electrode material. Here, the negative electrode material can be a carbon-based material (e.g., graphite, hard carbon, soft carbon), a silicon-based material (e.g., silicon oxide), or a carbon-silicon composite material. In the secondary battery, the positive electrode material and the negative electrode material can desorb lithium ions to achieve energy storage and release. The electrolyte is a medium for transporting lithium ions between the positive electrode sheet and the negative electrode sheet. The separator is permeable to lithium ions but not to electricity, separating the positive and negative electrode sheets to prevent short circuits. In general, the positive and negative electrode materials are very important for the energy storage function of lithium batteries, as well as the cell's energy density, cycle performance, safety, and other key performance factors.

[0025] In the secondary battery, the positive electrode material includes a first active material and a second active material. The first active material is a layered structure material such as lithium cobalt oxide, lithium nickel cobalt manganese oxide, or lithium nickel cobalt aluminate. The second active material is an olivine structure material such as lithium iron phosphate or lithium iron manganese phosphate. In the positive electrode material, the mass ratio of the first active material to the total mass of the first active material and the second active material is 70% by weight to 95% by weight. The mass ratio of the second active material to the total mass of the first active material and the second active material is 5% by weight to 30% by weight. For example, in some embodiments, the mass percentage of the first active material is 95%, 90%, 85%, 80%, 75%, or 70% by weight, and correspondingly, the mass percentage of the second active material is 95%, 90%, 85%, 80%, 75%, or 70% by weight, and 5%, 10%, 15%, 20%, 25%, or 30% by weight.

[0026] In the present invention, the first active material and the second active material may further include a nonmetallic element, for example, the nonmetallic element includes at least one of fluorine, phosphorus, boron, chlorine, silicon, and sulfur, and these elements can further improve the stability of the positive electrode active material.

[0027] The material form of the first active material is not limited. For example, the first active material may be single crystal, polycrystal, or a mixture of single crystal and polycrystal. In some embodiments, the first active material is polycrystal.

[0028] As shown in Figures 1 to 3, the positive electrode material of the secondary battery includes a layered structure material and an olivine structure material, so the discharge curve of the secondary battery has a first voltage platform with a higher voltage and a second voltage platform with a lower voltage. The measured voltage y in the discharge process of the secondary battery is between the first voltage platform and the second voltage platform. The measured voltage is the operating voltage of the secondary battery during discharge, which usually refers to the potential difference between the positive and negative electrodes of the battery under normal operating conditions. Specifically, the measured voltage y of the secondary battery is y1 min <y<y1 max Or y2 min <y<y2 max and y1 and y2 satisfy the formulas (1) and (2). y1=0.5265a+d (1) y2=-0.5265b+c (2) In the formula, a is the mass ratio of the first active material to the sum of the masses of the first active material and the second active material, b is the mass ratio of the second active material to the sum of the masses of the first active material and the second active material, c is a first voltage platform at which the first active material participates in the discharge, the first voltage platform being 3.7143V to 3.7743V, and d is a second voltage platform at which the second active material participates in the discharge, the second voltage platform being 3.1878V to 3.2478V.

[0029] Specifically, as shown in FIG. 2 and FIG. 3, the measured voltage y of the secondary battery is y1 min <y<y1 max In the formula, y1 min =0.5265a+3.1878 and y1 max =0.5265a+3.2478. Alternatively, the measured voltage y of the secondary battery is y2 min <y<y2 max where y2 min =-0.5265b+3.7143 and y2 max =-0.5265b+3.7743.

[0030] As shown in Figures 1 to 3, the layered structure material and olivine structure material mixed in the positive electrode material not only introduce the first voltage platform and the second voltage platform during the discharge process of the secondary battery, but also ensure that the measured voltage of the secondary battery does not decay excessively. Based on the change in the mass proportion b of the second active material, the measured voltage during discharge of the secondary battery is maintained at 3.55V to 3.75V. For example, in the positive electrode material, when the mass proportion of the second active material relative to the sum of the masses of the first active material and the second active material is 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, or 30 wt%, the corresponding measured voltage of the secondary battery during discharge is 3.72V, 3.70V, 3.68V, 3.66V, 3.63V, or 3.61V, respectively. In this operating voltage range, the secondary battery can maintain a high discharge efficiency.

[0031] As shown in FIG. 1 to FIG. 3, in the discharge curve of the secondary battery, the curve ratio of the introduced second voltage platform is positively correlated with the mass content of the olivine structure material mixed in the positive electrode material. In some embodiments, the curve ratio of the second active material involved in the discharge in the discharge curve is 80% to 87% of the mass ratio b of the second active material. For example, in some examples, when the mass ratio b of the second active material in the positive electrode material is 5% to 30% by weight, the curve ratio of the second active material involved in the discharge is 4% to 25%. In the secondary battery, as the mass ratio of the positive electrode material mixed with the olivine structure material increases, the discharge depth of the second voltage platform in the discharge curve increases, so that the thermal runaway temperature of the secondary battery also increases, and the thermal stability performance of the battery is significantly improved.

[0032] In some embodiments, the layered structure material is LiNi x Co y M 1-x-yO2, where 0 < x < 1 and 0 < y < 1. In some embodiments, element M is selected from one or more combinations of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, and Ta. That is, element M can be any one of the elements listed above, such as Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, or Ta. Element M can also be any combination of two or more of the elements listed above. For example, element M can be a combination of Mn and Zr, a combination of Mn and Mg, a combination of Al and Ti, a combination of Al and Zn, a combination of Mn, Al, and Ga, or a combination of Mn, Al, Cu, Mg, etc., which are not listed one by one here.

[0033] The olivine structure material is LiFe z G 1-z PO4, where 0 < z < 1. In some embodiments, element G is selected from one or more combinations of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, and Ta. That is, element G can be any one of the elements listed above, such as Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, or Ta. Element G can also be any combination of two or more of the elements listed above. For example, element G can be a combination of Mn and Zr, a combination of Mn and Mg, a combination of Al and Ti, a combination of Al and Zn, a combination of Mn, Al, and Ga, or a combination of Mn, Al, Cu, Mg, etc., which are not listed one by one here.

[0034] Also, when element M and element G are in a combination of two or more, the combination ratio of each element is not particularly limited, and the elements can be mixed in any ratio. In other embodiments, element M and element G can be types of elements not listed above.

[0035] In some embodiments, the average particle size D50 of the first active material is 0.5 μm to 5 μm, for example, the average particle size D50 of the first active material can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm. The average particle size D50 of the second active material is 0.3 μm to 3 μm, for example, the average particle size D50 of the second active material can be 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm, or 3 μm.

[0036] Here, within the above particle size range, the particle size distributions of the first and second active materials overlap. After mixing and rolling the first and second active materials, the positive electrode material has good uniformity, and the contact interface between the first and second active materials mixed in the positive electrode material has good affinity. In this way, the conductive efficiency of the positive electrode material is ensured, and the structural stability of the positive electrode material is also improved, so that the thermal safety performance of the secondary battery is further improved.

[0037] In some embodiments, the orientation degree of the positive electrode sheet is 70 to 99. For example, the orientation degree of the positive electrode sheet may be 70, 75, 80, 85, 90, 95, or 99. Here, as shown in Fig. 4, the orientation degree of the positive electrode sheet is Qc = C003 / C110, where C003 is the peak area of ​​the 003 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode sheet, and C110 is the peak area of ​​the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode sheet. The diffraction angle of the 003 characteristic peak is in the range of 17° to 19.5°, and the diffraction angle of the 110 characteristic diffraction peak is in the range of 65° to 66.5°.

[0038] In some embodiments, the degree of orientation of the negative electrode sheet may be 10 to 60, for example, the degree of orientation of the negative electrode sheet may be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60. Here, as shown in FIG. 5, the degree of orientation of the negative electrode sheet is Qc=C004 / C110. C004 is the peak area of ​​the 004 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode sheet, and C110 is the peak area of ​​the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode sheet. The diffraction angle of the 004 characteristic peak is in the range of 54° to 56°, and the diffraction angle of the 110 characteristic diffraction peak is in the range of 76° to 78°.

[0039] The present inventors have found that the mechanical performance of the positive electrode sheet and the negative electrode sheet is most excellent when the orientation degree of the positive electrode sheet is 70 to 99, and the orientation degree of the negative electrode sheet is 10 to 60. Since lithium ions are smoothly released from the positive and negative electrode sheets, the charge / discharge performance, cycle performance, and safety performance of the lithium ion battery are improved.

[0040] In the present invention, the positive electrode sheet is subjected to an XRD scanning test according to the JIS K 0131-1996 standard, and the negative electrode sheet is subjected to an XRD scanning test according to the JB / T4220-2011 standard. For example, the installed electrode sheet is X-ray scanned at a scanning speed of (1 / 4)° / min, and X-ray diffracted light is scanned and received at different diffraction angles using a 0.2 mm wide probe to obtain an X-ray spectrum of the test electrode sheet. Here, in the positive electrode sheet, the diffraction angle of the 003 diffraction characteristic peak is in the range of 17° to 19.5°, and the diffraction angle of the 110 diffraction characteristic peak is in the range of 65° to 66.5°. In the negative electrode sheet, the diffraction angle of the 004 diffraction characteristic peak is in the range of 54° to 56°. In the negative electrode sheet, the scanning range of the diffraction angle of the 110 diffraction characteristic peak is 76° to 78°.

[0041] In some embodiments, the positive electrode sheet has a compressed density of 3.0 g / cm 3 ~3.6g / cm 3 For example, 3.0 g / cm 3 , 3.1g / cm 3 , 3.2g / cm3 , 3.3g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 , or 3.6 g / cm 3 The surface density of the coating on one side of the positive electrode sheet may be 0.014 g / cm 2 ~0.02g / cm 2 For example, 0.014 g / cm 2 , 0.015g / cm 2 , 0.016g / cm 2 , 0.017g / cm 2 , 0.018g / cm 2 , 0.019g / cm 2 , or 0.020 g / cm 2 It's okay to be.

[0042] In some embodiments, the negative electrode sheet has a compressed density of 1.1 g / cm 3 ~1.7g / cm 3 For example, 1.1 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , or 1.7 g / cm 3 The surface density of the coating on one side of the negative electrode sheet may be, for example, 0.008 g / cm 2 , 0.009g / cm 2 , 0.010g / cm 2 , 0.011g / cm 2 , 0.012g / cm 2 , or 0.013 g / cm 2 It's okay to be.

[0043] In addition, in the present invention, the compression density and surface density of the positive electrode sheet and the negative electrode sheet are one-sided values, and the test method can refer to the conventional test method used by those skilled in the art. For example, the surface density of the electrode sheet is first determined by testing, and then the compression density of the electrode sheet is determined by dividing the surface density by the thickness of the electrode sheet.

[0044] Furthermore, the inventors have found through their research that when a lithium-ion battery including a composite positive electrode material (i.e., a positive electrode material including both a first active material and a second active material) satisfies the above-mentioned multiple parameter constraints, the charge / discharge performance, cycle performance, and safety performance of the resulting lithium-ion battery can reach the best state, so as to meet the practical needs of use, and have a low usage cost.

[0045] The composition and manufacturing method of the secondary battery provided by the present invention will be described in detail below.

[0046] In the preparation of the positive electrode sheet, the positive electrode material, the conductive agent, and the binder were mixed according to a mass ratio of (90-99):1.5:1.5, with a preferred mass ratio being 97:1.5:1.5. N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was thoroughly stirred to obtain a positive electrode slurry. The positive electrode slurry was applied onto a positive electrode current collector aluminum foil, and the positive electrode sheet was prepared through processes such as drying, cold pressing, and cutting. Here, the conductive agent can be selected from at least one conductive material such as Super P (SP) (carbon black), acetylene black, carbon nanotubes (CNT), graphene, and nano carbon fiber (VGCF). For example, when the conductive agent is SP and CNT, the mass ratio of SP and CNT was 1:0.5. The binder can be selected from at least one of PVDF, PTFE, and the like.

[0047] Here, the method for producing the positive electrode material includes the following steps.

[0048] The first active material and the second active material were mixed uniformly according to a mass ratio of (70-95):(5-30) to obtain a mixture. The mixture was rolled to obtain a positive electrode material. Here, the first active material is a layered structure material such as lithium cobalt oxide, lithium nickel cobalt manganate, or lithium nickel cobalt aluminate. The second active material is an olivine structure material such as lithium iron phosphate or lithium manganese iron phosphate.

[0049] In the preparation of the negative electrode sheet, the negative electrode material such as graphite, the conductive agent acetylene black, the thickener CMC (sodium carboxymethylcellulose), and the binder SBR (styrene butadiene rubber) were mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water was added, and the mixture was thoroughly stirred to obtain a negative electrode slurry. The negative electrode slurry was uniformly applied onto the negative electrode current collector copper foil, and the negative electrode sheet was prepared through processes such as drying, cold pressing, and slitting.

[0050] In preparing the separator, the material is a PE or PP porous membrane as the separator, and is preferably a PP / PE / PP porous membrane having a thickness of 9 μm to 18 μm (e.g., 9 μm, 12 μm, 16 μm, or 18 μm), an air permeability of 180 sec / 100 mL to 380 sec / 100 mL (e.g., 180 sec / 100 mL, 280 sec / 100 mL, or 380 sec / 100 mL), and a porosity of 30% to 50% (e.g., 30%, 40%, or 50%).

[0051] In preparing the electrolyte, EC (ethylene carbonate), DMC (dimethyl carbonate), and EMC (ethyl methyl carbonate) were mixed in a mass ratio of 1:1:1 to obtain an organic solvent. Next, a sufficiently dried lithium salt LiPF6 was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0052] In assembling the battery, the prepared positive electrode sheet, separator, and negative electrode sheet were stacked in order, and a separator was placed between the positive electrode sheet and the negative electrode sheet to provide insulation. Then, it was covered with an aluminum plastic film, dried, and then the electrolyte prepared above was injected. After sealing, leaving, chemical formation, and other processes, a pouch battery (lithium ion battery) with a capacity of 1 Ah was finally obtained.

[0053] The specific process and conditions for forming the electrolyte are provided below. After the electrolyte is injected, the battery is maintained in a high temperature and pressure environment of 0.1 MPa, and is charged at 45°C and 0.02°C for 17 minutes in a stationary state, and then charged to 0.3 Ah at 0.02°C after leaving it for 5 minutes. The airbag is then separated and vacuum sealed, and the electrolyte is left at room temperature for 48 hours to complete the formation of the electrolyte.

[0054] The technical solutions of the present invention will be described in detail below through some specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by conventional methods in the art.

[0055] Example 1

[0056] In this embodiment, a secondary battery is provided, and a process for preparing the secondary battery is provided as follows.

[0057] (1) In the preparation of the positive electrode sheet, the positive electrode material, conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 97:1.5:1.5. N-methylpyrrolidone (NMP) was added as a solvent to the mixture and thoroughly stirred to obtain a positive electrode slurry. The mixture was stirred using a vacuum mixer until it became uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry was uniformly applied onto a 16 μm aluminum foil current collector. The aluminum foil current collector was dried at room temperature, then transferred to an oven and dried at 80°C to 120°C for 6 hours. Then, cold pressing and slitting were performed to obtain a positive electrode sheet.

[0058] Here, the positive electrode material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 The positive electrode material was prepared by uniformly mixing the first active material NCM and the second active material LFP in a mass ratio of 95:5 to obtain a mixture, and then rolling the mixture to obtain the positive electrode material.

[0059] (2) In the preparation of the negative electrode sheet, graphite as the negative electrode material, acetylene black as the conductive agent, sodium carboxymethylcellulose (CMC) as the thickener, and styrene butadiene rubber (SBR) as the binder were mixed in a mass ratio of 96.4:1:1.2:1.4, and then deionized water was added. After adjusting the solid content concentration of the slurry to 55%, the mixture was thoroughly stirred and mixed using a vacuum mixer to obtain the negative electrode slurry. The negative electrode slurry was evenly applied to both sides of an 8 μm negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for drying. Thereafter, cold pressing, slitting, etc. were performed to obtain a negative electrode sheet.

[0060] (3) For the preparation of the electrolyte, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 in an argon atmosphere glove box with a water content of less than 10 ppm to obtain an organic solvent. Next, the lithium salt LiPF6 that had been thoroughly dried was dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0061] (4) In preparing the separator, a 9 μm polyethylene separator with a 2 μm ceramic coating on both sides was used.

[0062] (5) In the battery assembly, the obtained positive electrode sheet, separator, and negative electrode sheet were stacked in order, and a separator was placed between the positive electrode sheet and the negative electrode sheet to provide insulation. It was then covered with an aluminum plastic film, transferred to a vacuum oven at 120°C for drying, and 3.0g / Ah of electrolyte was injected and then sealed. After going through processes such as standing, hot pressing, cold pressing, chemical formation, clamping, and grading, a pouch battery (i.e., a lithium-ion battery) with a capacity of 1Ah was finally obtained.

[0063] The specific process and conditions for forming the electrolyte are provided below. After the electrolyte is injected, the battery is maintained in a high temperature and pressure environment of 0.1 MPa, charged at 45°C and 0.02°C for 17 minutes in a stationary state, left for 5 minutes, and then charged to 0.3 Ah at 0.02°C. The airbag is then separated and vacuum sealed, and the electrolyte is left at room temperature for 48 hours to complete the formation of the electrolyte.

[0064] Example 2

[0065] In this embodiment, a secondary battery of the same system as that of the first embodiment is provided. The difference between this embodiment and the first embodiment is that the positive electrode material of the positive electrode sheet is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass fraction b of 10 wt%.

[0066] Example 3

[0067] In this embodiment, a secondary battery of the same system as in Example 1 is provided. The difference between this embodiment and Example 1 is that the positive electrode material of the positive electrode sheet is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass fraction b of 15 wt%.

[0068] Example 4

[0069] In this embodiment, a secondary battery of the same system as in Example 1 is provided. The difference between this embodiment and Example 1 is that the positive electrode material of the positive electrode sheet is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass fraction b of 20 wt.%.

[0070] Example 5

[0071] In this embodiment, a secondary battery of the same system as in Example 1 is provided. The difference between this embodiment and Example 1 is that the positive electrode material of the positive electrode sheet is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass fraction b of 25 wt.%.

[0072] Example 6

[0073] In this embodiment, a secondary battery of the same system as in Example 1 is provided. The difference between this embodiment and Example 1 is that the positive electrode material of the positive electrode sheet is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM) and lithium iron phosphate (LiFePO4, LFP) with a mass fraction b of 30 wt.%.

[0074] Comparative Example 1

[0075] In this comparative example, a secondary battery of the same system as in Example 1 is provided. The difference between this comparative example and Example 1 is that the positive electrode material of the positive electrode sheet is not mixed with the second active material lithium iron phosphate (LiFePO4, LFP), but with the first active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM).

[0076] A discharge test and a nail penetration test were performed on the secondary batteries produced in Examples 1 to 6 and Comparative Example 1 to verify the difference in safety performance between the secondary batteries of the Examples and Comparative Example.

[0077] Discharge Curve Test:

[0078] At 25°C, the secondary battery was charged to the upper cutoff voltage at a constant current of 0.1 C, charged at a constant voltage until the current became less than 0.05 C, and then discharged to the lower cutoff voltage at a constant current of 0.1 C after leaving it for 10 minutes. The discharge capacity curve at this time is the discharge curve.

[0079] In the nail penetration test, the secondary battery was fully charged to SOC 100%. A steel needle with a diameter of 8 mm was used to pierce the secondary battery at a speed of 25 mm / s. After one hour of observation, the maximum temperature of the secondary battery cell was collected. If the secondary battery did not ignite, it was considered to have passed the nail penetration test. If the secondary battery ignited, the elapsed time from ignition to ignition was recorded.

[0080] Measurement voltage test:

[0081] The secondary battery was discharged at a standard rate of 1 C. The energy released by discharging the secondary battery was divided by its capacity to obtain the actual measured voltage.

[0082] The test results of the secondary batteries of Examples 1 to 6 and Comparative Example 1 are shown in Table 1.

[0083] Table 1: Discharge performance and safety performance tests of secondary batteries of Examples 1 to 6 and Comparative Example 1

[0084] [Table 1]

[0085] Comparing the test results of Examples 1 to 6 and Comparative Example 1, it can be seen that by mixing LFP into the positive electrode material mainly composed of NCM, the thermal stability of the positive electrode material is effectively improved, and the safety performance of the secondary battery is significantly improved. Here, by adding LFP to the positive electrode material, during the discharge process of the secondary battery, the LFP participates in the second voltage platform of the discharge, thus effectively reducing the discharge depth of the layered structure material under the high voltage platform, improving the structural thermal stability of the positive electrode material, and avoiding the rapid drop in the thermal runaway temperature of the battery caused by over-discharge. This significantly improves the safety performance of the secondary battery.

[0086] Comparing the test results of Examples 1 to 6, as the mass fraction b of the LFP material added to the positive electrode material increases, the curve ratio in which NCM is involved in the discharge in the discharge curve of the secondary battery decreases. Accordingly, the curve ratio in which LFP is involved in the discharge increases, and the maximum temperature of the secondary battery in the nail penetration process also drops significantly. For example, when the mass fraction b of the LFP material in the positive electrode material increases from 5 wt% to 20 wt%, the maximum temperature of the secondary battery in the nail penetration process drops from 210°C to 30°C.

[0087] Furthermore, from the test results of Examples 3 to 6, it can be seen that when the mass proportion b of LFP exceeds 20% by weight, increasing the mass content of LFP in the positive electrode material does not have a significant effect on improving the thermal safety performance of the secondary battery. Instead, the measured voltage of the secondary battery further decreases during discharge. For example, when the mass proportion b of the LFP material in the positive electrode material increases from 20% by weight to 30% by weight, the maximum temperature of the secondary battery in the nail penetration process only decreases from 30°C to 28.5°C, while the measured voltage of the secondary battery continues to decrease from 3.66V to 3.61V. It can be seen that in the positive electrode material, the mass proportion b of the second active material LFP is preferably 20% by weight. This mass proportion of the positive electrode material can achieve the best improvement effect on the thermal safety performance of the secondary battery, provided that the measured voltage of the secondary battery does not significantly attenuate. [Industrial Applicability]

[0088] Furthermore, the secondary battery of the present invention can be used in the field of electronics and has high industrial applicability.

[0089] The above-described embodiments are illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Those skilled in the art may modify or change the above-described embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical ideas disclosed in the present invention are also intended to be included in the scope of the claims of the present invention.

Claims

1. A secondary battery including a positive electrode sheet, a separator, an electrolyte, and a negative electrode sheet, The positive electrode sheet includes a positive electrode material including a first active material that is a layered structure material and a second active material that is an olivine structure material; The mass ratio of the second active material to the total mass of the first active material and the second active material is 5% by weight to 30% by weight, the discharge curve of the secondary battery includes a first voltage platform and a second voltage platform, and the measured voltage y of the secondary battery is y1 min <y<y1 max Or y2 min <y<y2 max and y1 and y2 satisfy the formulas (1) and (2). y1=0.5265a+d (1) y2=-0.5265b+c (2) In the formula, a is the mass fraction of the first active material relative to the sum of the masses of the first active material and the second active material, b is the mass fraction of the second active material relative to the sum of the masses of the first active material and the second active material, c is the first voltage platform to which the first active material participates in discharging, the first voltage platform being between 3.7143V and 3.7743V, and d is the second voltage platform to which the second active material participates in discharging, the second voltage platform being between 3.1878V and 3.2478V.

2. 2. The secondary battery according to claim 1, wherein a curve ratio value of the second active material participating in discharge in the discharge curve is 80% to 87% of the mass ratio b.

3. 3. The secondary battery according to claim 2, wherein a curve ratio of the second active material participating in the discharge curve is 4% to 25%.

4. The layered structure material is LiNi x Co y M 1-x-y O 2 2. The secondary battery of claim 1, wherein 0<x<1 and 0<y<1, and element M includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, and Ta.

5. The olivine structure material is LiFe z G 1-z P.O. 4 2. The secondary battery of claim 1, wherein 0<z<1 and element G includes one or more of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga, and Ta.

6. 2. The secondary battery according to claim 1, wherein the average particle diameter D50 of the first active material is 0.5 μm to 5 μm, and the average particle diameter D50 of the second active material is 0.3 μm to 3 μm.

7. The secondary battery according to claim 1 , wherein the first active material is monocrystalline and / or polycrystalline.

8. 2. The secondary battery according to claim 1, wherein the orientation degree of the positive electrode sheet is 70 to 99, and the orientation degree of the negative electrode sheet is 10 to 60.

9. The compressed density of the positive electrode sheet is 3.0 g / cm 3 ~3.6g / cm 3 The surface density of the coating on one side of the positive electrode sheet is 0.014 g / cm 2 ~0.02g / cm 2 The secondary battery according to claim 1 ,

10. The compressed density of the negative electrode sheet is 1.1 g / cm 3 ~1.7g / cm 3 The surface density of the coating on one side of the negative electrode sheet is 0.008 g / cm 2 ~0.013g / cm 2 The secondary battery according to claim 1 ,

11. The negative electrode sheet includes a negative electrode material, 2. The secondary battery according to claim 1, wherein the negative electrode material is a carbon-based material, a silicon-based material, or a carbon-silicon composite material.

12. The secondary battery according to claim 11 , wherein the negative electrode material is graphite, hard carbon, soft carbon, or silicon oxide.

13. The electrolyte includes EC, DMC, or EMC, and LiPF 6 and the separator comprises a PE, PP, or PP / PE / PP composite film.

14. The secondary battery according to claim 1, wherein the positive electrode material, the conductive agent, and the binder are mixed in a mass ratio of (90-99):1.5:1.5, N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is thoroughly stirred to obtain a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector aluminum foil, and the positive electrode sheet is produced through steps such as drying, cold pressing, and slitting.

15. 15. The secondary battery according to claim 14, wherein the conductive agent is selected from at least one conductive material of Super P (carbon black), acetylene black, carbon nanotubes (CNT), graphene, and nano carbon fiber (VGCF).

16. The secondary battery according to claim 15, wherein the conductive agent is made of Super P and CNT, the mass ratio of Super P to CNT is 1:0.5, and the binder is selected from at least one of PVDF and PTFE.

17. The method for preparing the positive electrode material includes the steps of uniformly mixing the first active material and the second active material according to a mass ratio of (70-95):(5-30) to obtain a mixture, and rolling the mixture to obtain the positive electrode material. The secondary battery according to claim 14.

18. the first active material is a layered structure material including lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminate; 18. The secondary battery according to claim 17, wherein the second active material is an olivine structure material including lithium iron phosphate or lithium manganese iron phosphate.

19. 15. The secondary battery according to claim 14, wherein in the preparation of the negative electrode sheet, the negative electrode material including graphite, a conductive agent, and acetylene black, a thickener CMC (sodium carboxymethylcellulose), and a binder SBR (styrene butadiene rubber) are mixed in a mass ratio, deionized water is added, and the mixture is thoroughly stirred to obtain a negative electrode slurry.

20. The negative electrode slurry is uniformly applied onto a negative electrode current collector copper foil, The secondary battery according to claim 19 , wherein the negative electrode sheet is produced through a process of drying, cold pressing, and slitting.

Citation Information

Patent Citations

  • Positive electrode active material, and positive electrode and lithium battery adopting the same

    JP2012190786A

  • Nonaqueous electrolyte secondary battery and method for manufacturing the same

    JP2015228282A

  • Nonaqueous electrolyte secondary battery

    JP2016058187A

  • A large two-stroke uniflow scavenged turbocharged internal combustion engine configured for reducing ammonia slip and a method for reducing ammonia slip of such an engine

    KR1020240046056A

  • Printing system for display panel side terminal

    KR102077520B1